How many in a crowd? Assessing overcrowding measures in Australian housing - Dockery, Alfred Michael; Harris, Mark; Moskos, Megan; Isherwood, Linda (AHURI, 2022)
This study assess the measurement of overcrowding in Australia and explores the relationships between various household density measures and the wellbeing of occupants. Indicators of the incidence or severity of household crowding in Australia actually measure occupant density—the ratio of occupants to available space—rather than crowding, which relates to a psychological response to the sense of excessive density. How overcrowding is defined and measured has important implications for funding requirements, the appropriate mix of housing stock given household structures and rules for allocating families to public and community housing.
Final Report No. 382
Keywords: Families and relationships; Health and wellbeing; Housing, communities and neighbourhoods; Surveys and survey methodology